Comprehensive Analysis of the Expression and Prognosis for ITGBs: Identification of ITGB5 as a Biomarker of Poor Prognosis and Correlated with Immune Infiltrates in Gastric Cancer - Liu, Dongliang; Liu, Shaojun; Fang, Yu; Liu, Liu; Hu, Kongwang (Frontiers in Cell and Developmental Biology, 2022)
Background: Integrin β superfamily members (ITGBs) are documented to play important roles in various biological processes, and accumulating evidence suggests that ITGBs are associated with carcinogenic effects in several malignancies. Gastric cancer (GC) is a complicated and highly heterogeneous disease; however, the expression and prognostic values of eight ITGBs and potential mechanism in GC remain largely unclear. Methods: The expression and prognostic significance of ITGBs in GC were systematically analyzed through Gene Expression Profiling Interactive Analysis, Human Protein Atlas, Kaplan–Meier Plotter, and cBioPortal databases. Then, the mRNA transcription data and corresponding clinical data of GC were downloaded from the Gene Expression Omnibus database as a testing cohort, and differentially expressed and prognostic genes were identified. The correlation between ITGB5 expression and overall survival and various clinical parameters were found by using univariate/multivariable Cox regression and Kaplan–Meier survival analysis. Additionally, differential analysis of gene expression profiles in low- and high-ITGB5 expression groups and pathway enrichment analysis was performed. Finally, the correlation of ITGB5 expression with immune infiltrates in GC was clarified. Results: Compared with adjacent normal tissue, the results reveal that the mRNA levels of ITGB1-2 and ITGB4-8 are significantly higher in GC, and immunohistochemistry results show the consistency between RNA and protein expression levels. Cox regression and Kaplan–Meier survival analysis indicate that high ITGB5 expression contributes to a poor prognosis and could be an independent prognostic factor in GC patients. Besides this, gene functional enrichment analysis indicates that ITGB5 expression is significantly associated with extracellular matrix organization, cell-substrate adhesion, and ossification. The KEGG pathway analysis of ITGB5 shows a close association between ITGB5 and focal adhesion, ECM-receptor interaction, phagosome, and PI3K-Akt signaling pathway. Last, the infiltrating level of CD4+ T cells, macrophages, and dendritic cells are positively related to the expression of ITGB5, especially macrophages, and lower levels of macrophages predict a better prognosis in GC in our study. Conclusion: Our findings investigate that ITGB5 may function as a valid biomarker of prognosis, and high expression of ITGB5 predicts poor prognosis for patients with GC. Besides this, it might be a potential target of precision therapy against GC.